Identifying Cultural Tourism Potential in Grogol Village, Gunungkidul: A Market Appeal–Robusticity Matrix Approach - Rina Widiastuti; Nuryuda Irdana (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to identify and evaluate the cultural tourism potential of Kalurahan Grogol in Gunungkidul Regency to inform the development of a community-based cultural tourism village. The research employed a qualitative descriptive approach supported by quantitative scoring techniques using a 1–5 Likert scale across four assessment dimensions: cultural value, physical value, tourism value, and experiential value. The analysis applied Du Cros and McKercher’s Market Appeal–Robusticity Matrix to map the market attractiveness and cultural robustness of each cultural asset. Data were collected through semi-structured interviews, observations, and documentation studies of 46 tangible and intangible cultural assets in Kalurahan Grogol. The findings reveal that most cultural assets exhibit moderate to high cultural robustness, indicating that local cultural practices remain active and socially sustained within the community. Prominent cultural assets such as Rasulan, Karawitan Lestari Budoyo, Reog Sedyo Laras, Gejlok Lesung, Sega Berkat, and Tempe Godhong are positioned in Quadrant A1, characterized by high market appeal and high robustness, making them highly potential as leading cultural tourism attractions. Meanwhile, assets in Quadrants B and C present opportunities to develop creative, educational, spiritual, and wellness-based experiential tourism products. The study also finds that several sacred traditions categorized in Quadrant D are more appropriately preserved through non-commercial approaches. The absence of cultural assets in the D3 category indicates that the cultural system of Kalurahan Grogol remains adaptive and regenerative amid modernization. This research contributes theoretically by extending the application of the Market Appeal–Robusticity Matrix into the context of community-based cultural tourism villages. It provides strategic recommendations for sustainable cultural tourism development that remain sensitive to local cultural authenticity.